Evaluation of protocorm formation in meristematic regions of roots and leaves of Miltonia spectabilis moreliana (Orchidaceae). - Pedroso-de-Moraes, Cristiano; Souza-Leal, Thiago de; Pires Corrêa, Rodrigo; Leme Paioli, Renaze Raiane; Aurélio Marteline, Marco (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
The aim of this study was to evaluate the effect of 2.4-D and BAP on protocorm formation in meristematic regions of root and leaf of Miltonia spectabilis moreliana, and to test the effect of sucrose concentrations and pH levels on the growth of protocorms. Root and leaf segments of in vitro-germinated plants were cultured in MS/2 culture medium supplemented with 2.4-D and BAP, and kept in the dark for 210 days. The combination of 3 mg.L-1 2.4-D and 1 or 3 mg.L-1 BAP provided the best results. The concentrations of 15 and 30 g.L-1 sucrose, independently of the pH, were more efficient for the in vitro culture of this species, as they promoted an increase in the number and length of roots, height, and fresh weight of the plantlets. The pH was significant only in combination with 15 g.L-1 sucrose for the length of the largest root and fresh weight.